2020
DOI: 10.1016/j.watres.2020.116404
|View full text |Cite
|
Sign up to set email alerts
|

Making waves: Wastewater-based epidemiology for COVID-19 – approaches and challenges for surveillance and prediction

Abstract: Highlights Presence of SARS-CoV-2 in feces and wastewater constitutes a paradigm shift in surveillance. WBE has potential as a surveillance and predictive tool during the COVID-19 pandemic. Validated protocols for concentration and quantification of SARS-CoV-2 and other markers are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
293
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(302 citation statements)
references
References 65 publications
6
293
0
3
Order By: Relevance
“…Our findings highlight the use of WBE approach as an early warning system for the emergence of new COVID-19 cases enabling faster prevention and public health actions by the State, as emphasized recently ( Farkas et al., 2020 ; Medema et al., 2020 ; Polo et al., 2020 ; Randazzo et al., 2020 ; Thompson et al., 2020 ). The success of the intervention carried out in the Boa Esperança community, resulted in the inclusion of SARS-CoV-2 sewage data as a complementary indicator to other traditionally health indicators used, such as growth rates of new cases and hospitalizations, mortality rate, number of available hospital beds and bed occupancy rate.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Our findings highlight the use of WBE approach as an early warning system for the emergence of new COVID-19 cases enabling faster prevention and public health actions by the State, as emphasized recently ( Farkas et al., 2020 ; Medema et al., 2020 ; Polo et al., 2020 ; Randazzo et al., 2020 ; Thompson et al., 2020 ). The success of the intervention carried out in the Boa Esperança community, resulted in the inclusion of SARS-CoV-2 sewage data as a complementary indicator to other traditionally health indicators used, such as growth rates of new cases and hospitalizations, mortality rate, number of available hospital beds and bed occupancy rate.…”
Section: Discussionsupporting
confidence: 59%
“…Detection of SARS-CoV-2 in faeces and early shedding demonstrated by virus detection in faeces ( He et al., 2020 ) resulted in use of an environmental approach called wastewater-based epidemiology (WBE) as an additional tool to support COVID-19 prevention and control actions in several regions ( Farkas et al., 2020 ; Hart and Halden, 2020 ; Mao et al., 2020 ; Thompson et al., 2020 ). According to Polo et al. (2020) , WBE consists on the assumption that any stable substance that is excreted by humans and in wastewater can be used to back-calculate the original concentration excreted by the serviced population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous WBE work identified several possible normalization biomarkers in wastewater such as 5-Hydroxyindoleacetic acid ( Chen et al, 2014 ), caffeine and cotinine ( Rico et al, 2017 ). However, due to the higher incidence of SARS-CoV-2 viral particles in feces as compared to urine ( Collivignarelli et al, 2020 ; Jeong et al, 2020 ; Lodder and de Roda Husman, 2020 ; Zhurakivska et al, 2020 ), other biomarkers present in wastewater solids, such as pepper mild mottle virus (PMMoV) ( Jafferali et al, 2020 ; Kitajima et al, 2018 ; Rosario et al, 2009 ; Symonds et al, 2014 ) and crAssphage ( Crank et al, 2020 ; Polo et al, 2020 ) saw are being utilized for the normalization of SARS-CoV-2. Some recent studies have demonstrated that biomarker normalized SARS-CoV-2 viral signal may in fact track be capable of tracking the incidence of COVID-19 infections in the community ( Gerrity et al, 2021 ; Kitamura et al, 2021 ) more effectively than non-biomarker-normalized viral signal ( Jafferali et al, 2020 ; Wu et al, 2020 ), even if accounting for corrections due to flow or solids mass flux ( D'Aoust et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in order to estimate the infection rate in a community, it is necessary to accurately measure the community population, i.e. the population normalization for the data [32]. This is a challenging task for areas with high population mobility.…”
Section: Introductionmentioning
confidence: 99%